Effects of large extra dimensions on cosmogenic neutrino fluxes - Reynoso, Matias Miguel (2013)
We study the consequences of theories with extra dimensions and a gravity scale of a few TeVs on the cosmogenic flux of neutrinos. Taking into account the most recent upper limits for the onset of the gravity effects given by the LHC, and the updated predictions for the cosmogenic neutrino flux consistent with Fermi-LAT data, we compute the expected number of shower events to be detected with new generation acoustic detectors such as ARA.